Cinderella - McClintock, Barbara; Perrault, Charles, 1628-1703. (New York : Walt Disney Company, 1994)
Although mistreated by her stepmother and stepsisters, Cinderella meets her prince with the help of her fairy godmother.
Keywords: Fairy tales